Planning benchmark study for SBRT of early stage NSCLC - Moustakis, Christos; Blanck, Oliver; Sterzing, Florian (Strahlentherapie und Onkologie, 2017)
PurposeThe aim was to evaluate stereotactic body radiation therapy (SBRT) treatment planning variability for early stage nonsmall cell lung cancer (NSCLC) with respect to the published guidelines of the Stereotactic Radiotherapy Working Group of the German Society for Radiation Oncology (DEGRO).Materials and methodsPlanning computed tomography (CT) scan and the structure sets (planning target volume, PTV; organs at risk, OARs) of 3 patients with early stage NSCLC were sent to 22 radiotherapy departments with SBRT experience: each department was asked to prepare a treatment plan according to the DEGRO guidelines. The prescription dose was 3 fractions of 15 Gy to the 65% isodose.ResultsIn all, 87 plans were generated: 36 used intensity-modulated arc therapy (IMAT), 21 used three-dimensional conformal radiation therapy (3DCRT), 6 used static field intensity-modulated radiation therapy (SF-IMRT), 9 used helical radiotherapy and 15 used robotic radiosurgery. PTV dose coverage and simultaneously kept OARs doses were within the clinical limits published in the DEGRO guidelines. However, mean PTV dose (mean 58.0 Gy, range 52.8-66.4 Gy) and dose conformity indices (mean 0.75, range 0.60-1.00) varied between institutions and techniques (p ≤ 0.02). OARs doses varied substantially between institutions, but appeared to be technique independent (p = 0.21).ConclusionAll studied treatment techniques are well suited for SBRT of early stage NSCLC according to the DEGRO guidelines. Homogenization of SBRT practice in Germany is possible through the guidelines; however, detailed treatment plan characteristics varied between techniques and institutions and further homogenization is warranted in future studies and recommendations. Optimized treatment planning should always follow the ALARA (as low as reasonably achievable) principle.